PERAN MODERASI BERAGAMA DALAM MENANGGULANGI PERILAKU BULLYING DI KALANGAN PELAJAR - Syalwa, Ana Tiara; Kholifah, Afiyatun (Universitas Muhammadiyah Tapanuli Selatan, 2025)
Bullying behavior among students is a serious problem in the education world that can have negative impacts on students' psychological and social development. One effective approach to addressing this phenomenon is by reinforcing the values of religious moderation. Religious moderation emphasizes a stance of tolerance, appreciation of differences, and the enforcement of justice and humanity values, which supports the creation of a safe and inclusive school environment. This research aims to explore the role of religious moderation in preventing and reducing bullying behavior among students. In this study, the researcher uses a literature study method with a descriptive approach, which involves the collection of data, examination, and analysis of various sources of literature. The findings of this study reveal that instilling values of moderation through various learning activities, extracurricular activities, and the exemplary behavior of teachers can shape students' characters to be tolerant, empathetic, and to steer clear of both verbal and physical violence. Thus, religious moderation plays a very important and significant role in efforts to prevent and educate against bullying in the school environment.